Evaluasi Kebijakan Ekonomi Publik dalam Mendorong Pertumbuhan Inklusif di Indonesia - Mufadhol, Allam Tri; Afandi, Angelika; Supriyatna, Daffa Muhammad; Al Anbari, Ghaelan Haerudin; Dewi, Sitta (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Inclusive economic growth is a strategic goal of development in Indonesia to ensure that the benefits of economic growth can be felt evenly by all levels of society. This study evaluates the effectiveness of Indonesia's public economic policies in promoting inclusive growth during the period 20142024. The study uses a descriptive qualitative approach relying on primary data from interviews and secondary data from policy documents, official reports, and literature reviews. The findings show that although fiscal policy, taxation systems, subsidy reforms, and fiscal decentralization have made various advances, their implementation still faces challenges in the form of budget allocation inequality, bureaucratic inefficiencies, weaknesses in tax administration, and disparities in development between regions. Subsidy and social protection reforms have begun to show positive directions in reducing poverty, but still require improvements in data accuracy and coordination between institutions. This study recommends data-based planning, strengthening governance, and increasing regional capacity as strategies to strengthen equitable and sustainable economic growth.